2008
DOI: 10.1177/0272989x08315240
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review: Health-State Utilities in Liver Disease: A Systematic Review

Abstract: The authors have created a valuable liver disease- based utility resource from which researchers and policy makers can easily view all available utility estimates from the literature. They have also estimated health-state utilities for major states of hepatitis C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
109
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(116 citation statements)
references
References 54 publications
5
109
0
Order By: Relevance
“…5,[16][17][18]20,[22][23][24][25][26][27][28][29][30][31][32] All cost data were expressed in Canadian dollars and were inflated to 2015 using the Statistics Canada Consumer Price Index for health care and personal items. 33 Treatment efficacy and safety inputs were generated directly from the network meta-analysis model.…”
Section: Model Parametersmentioning
confidence: 99%
“…5,[16][17][18]20,[22][23][24][25][26][27][28][29][30][31][32] All cost data were expressed in Canadian dollars and were inflated to 2015 using the Statistics Canada Consumer Price Index for health care and personal items. 33 Treatment efficacy and safety inputs were generated directly from the network meta-analysis model.…”
Section: Model Parametersmentioning
confidence: 99%
“…*The study 47 did not include patients with decompensated cirrhosis, so utility for these patients was determined by adjusting the chronic HCV infection utility score according to a disutility value published in the systematic review. 48 approach resulted in a net cost increment of $266 and 0.0077 QALYs gained per person, which translated to an incremental cost-effectiveness ratio of $34 783 per QALY gained (Table 3). We repeated the 4 screening strategies by considering 1-time screening for individuals 45-64 years of age.…”
Section: Model Validationmentioning
confidence: 99%
“…In response to Cortese et al, we clarify that in our analysis we used utilities reported in table 1 of our study 1 and that were similar to those reported in a meta-analysis by McLernon et al 6 using the EQ-5D. Specifically, the utilities we used were those reported by Sullivan et al, 7 and not by Liu et al, 8 as wrongly reported due to a misprint.…”
Section: Cost-effectiveness Analysis Of New Drugs For Chronic Hepatitmentioning
confidence: 73%